(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A lesson plan is an important methodological component of the learningprocess. The key purpose of the article is to analyse the current situation andsuggest how the information technologies can assist in the development oflesson plans, their accumulation and retrieval, thus ensuring their effectiveapplication. The development of lesson plans and descriptions will allow educatorsreuse didactic resources (lesson plans) as an effective learning tool. Thestorage of didactic resources will allow teachers to use the best practices,and the same learning objects in different learning scenarios. Planning ahead to identify a course of action that can effectively helplearners reach their goals and objectives is an important first step ineffective instruction. Lesson planning communicates to learners what they willlearn and how their goals will be assessed, and it helps instructors organizecontent, materials, time, instructional strategies, and assistance in theclassroom.